Methodologyforactivationtheprocessteaching-learninginthe discipline engineering of the human factor - Rodríguez García, Niurka; Lara Díaz, Lidia Mercedes (Revista Universidad de Guayaquil, 2016)
The discipline Engineering of the Human Factor in the training of Industrial Engineers its theoretical conception, is based on the analysis and solution of problems in production processes or services and the improvement of the man involved in them, being the case study the fundamental method to use in their subjects. In the teaching - learning process of each subject of the discipline, there are inadequacies in the ways of solution of the method by students. The objective of the work presented is to implement the methodology for the activation of the teaching - learning process in the Human Factor Engineering discipline, which allowed the student to identify, elaborate, analyze and solve cases in the work context, linking several teaching methods - learning.